Suitibility of Hair Goat Breeding with regards to Organic Production - Mahmut Keskin; Sabri Gül; Osman Biçer; Zuhal Gündüz (Turkish Journal of Agriculture: Food Science and Technology, 2017)
Although the intensification of agricultural production is the reason for feeding of increasing human population the demand for organic or ecological products is increasing in parallel with the social consciousness in recent years. Hair goat breeding is made in a large part of Turkey that is suitable or may become suitable for organic production system with a few arrangements. In this study, Hair goat breeding was evaluated together with the Regulation on the Principles and Implementation of Organic Agriculture. The study is important in terms of ensuring sustainability of hair goats under the threat of crossbreeding by assessing it within organic production.